Integrated landscape management for agriculture, rural livelihoods, and ecosystem conservation: an assessment of experience from Latin America and the Caribbean - Estrada-Carmona, Natalia; Hart, A.K.; DeClerck, Fabrice A.J.; Harvey, Celia A.; Milder, Jeffrey C. (Elsevier, 2014)
Approaches to integrated landscape management are currently garnering new interest as scientists, policymakers, and local stakeholders recognize the need to increase the multi-functionality of agricultural landscapes for food production, livelihood improvement, and ecosystem conservation. Such approaches have been attempted in many parts of Latin America and the Caribbean (LAC) but to date there has been no systematic assessment of their characteristics, outcomes, and limitations. To fill this gap, we surveyed participants and managers in integrated landscape initiatives throughout the LAC region to characterize these initiatives’ contexts, motivations and objectives, stakeholders and participants, activities and investments, outcomes, and major successes and shortcomings. Results from 104 initiatives in 21 countries indicate that integrated landscape management is being applied across the region to address a variety of challenges in diverse contexts, and that use of this approach is expanding. Initiatives reported investing across four key “domains” of landscape multi-functionality: agricultural production, ecosystem conservation, human livelihoods, and institutional planning and coordination. Initiatives reported positive outcomes across all four domains, but particularly with respect to institutional planning and coordination. Initiatives with larger numbers of objectives, investments, and participating stakeholder groups all reported significantly higher numbers of positive outcomes, suggesting significant value in the core precepts of the integrated landscape management approach. Key challenges identified by survey respondents—including the long time horizon required to achieve results at scale, unsupportive policy frameworks, and difficulty in engaging the private sector and other important stakeholders—offer insights for improving the future effectiveness of integrated landscape initiatives.